Fever - Meyer, Deon; Seegers, K. L. (New York : Atlantic Monthly Press ; [Emeryville, CA] : Distributed by Publishers Group West, 2017)
"Nico Storm and his father Willem drive a truck filled with essential supplies through a desolate land. They are among the few in South Africa -- and the world, as far as they know -- to have survived a devastating virus which has swept through the country. Their world turned upside down, Nico realizes that his superb marksmanship and cool head mean he is destined to be his father's protector, even though he is still only a boy. But Willem Storm, though not a fighter, is both a thinker and a leader, a wise and compassionate man with a vision for a new community that survivors will rebuild from the ruins. And so Amanzi is founded, drawing Storm's "homeless and tempest-tost" -- starting with Melinda Swanevelder, whom they rescued from brutal thugs; Hennie Flaai, with his vital Cessna plane; Beryl Fortuin, with her ragtag group of orphans; and Domingo, the man with the tattooed hand, whom Nico knows immediately is someone you want on your side. And then there is Sofia Bergman, the most beautiful girl that Nico has ever seen, who changes everything. So the community grows -- and with each step forward, as resources increase, so do the challenges they must face -- not just from the attacks of biker brigands, but also from within. As Nico undergoes an extraordinary rite of passage in this new world, he experiences hardship and heartbreak and has his loyalty tested to its limits. Looking back later in life, he recounts the events that led to the greatest rupture of all -- the hunt for the murderer of the person he loves most. An exhilarating new standalone from the author of the internationally bestselling Benny Griessel thriller series, Fever is a gripping epic like nothing else Meyer has written before --
"Originally published in Afrikaans in 2016 as Koors by Human & Rousseau. First published in Great Britain in 2017 by Hodder & Stoughton, a Hachette UK Company" -- Verso title page.
Keywords: Fathers and sons -- Fiction; Viruses -- Fiction; Regression (Civilization) -- Fiction; Survivalism -- Fiction; Maturation (Psychology) -- Fiction; South Africa -- Fiction; Suspense fiction; Psychological fiction